What is known about the nutritional intake of women with Hyperemesis Gravidarum?: A scoping review. (February 2021) - Maslin, Kate; Shaw, Victoria; Brown, Anne; Dean, Caitlin; Shawe, Jill
Highlights: Hyperemesis gravidarum (HG) is an extreme form of pregnancy nausea and vomiting. Women with HG are at risk of malnutrition, but little data exists on dietary intake. This review identified only four studies that measured diet in women with HG. Women with HG have highly deficient intakes of energy and nearly all nutrients. Further research evaluating dietary intake in this high-risk group is warranted. Abstract: Hyperemesis gravidarum (HG) is characterised by extreme nausea and vomiting of pregnancy, which can lead to dehydration, weight loss and electrolyte disturbances. Historically research has been challenging due to a lack of diagnostic criteria and objective outcome measures. Most studies in this population group have focused on medical management of symptoms, with little known about the effect of HG on nutritional intake and how this relates to perinatal outcomes. The aim of this study was to synthesise current knowledge of the dietary intake of women with HG. A systematic search of search engines was conducted in April 2020 using the following databases: MEDLINE, Embase, CINAHL, Cochrane database, Scopus, NHS Evidence, BNI, Emcare, ClinicalTrials.gov, PROSPERO, Ethos and Open Grey. Titles and abstracts were screened independently by two reviewers against predefined inclusion and exclusion criteria. Studies were included where the authors described severe pregnancy nausea and vomiting as HG, regardless of how HG was defined. After removal of duplicates, 4402 titles were identified, of which 3992 were initially excluded based on abstract and title. Following full text review, four of 10 articles were included. Three of the studies were hospital-based case control studies, one was an observational women's cohort study. Assessment of dietary intake was heterogeneous, with both retrospective and prospective self-report methods used, over different timeframes. In three of the studies, dietary intake was reported at one time point only. In total, across all four studies, data from only 314 women were included. Overall, despite data collected from four different countries, over 30 years, with various methods, women with HG had a significantly poorer dietary intake compared to non-affected pregnant women, consuming less than 50 % of recommended intakes for most nutrients. Nutritional intake worsened with increasing severity of symptoms. As this was a scoping review, study quality was not assessed. Overall, this review has identified a paucity of data about the dietary intake of women with HG; the limited available data indicates that women with HG are at risk of malnutrition. Future research quantifying nutritional intake in women with HG at several time points during pregnancy would provide valuable reference data, enabling nutritional status and outcomes to be monitored and interventions to be evaluated.